Antecedents of a healthcare tourism satisfaction: A case of developing economy. Issue 2 (4th October 2020) - Kumar, Anil; Singh, Rohit Kumar; Modgil, Sachin
Abstract : The focal intent of the study is to identify the vital determinants that bring satisfaction to health tourists along with their intent to visit the Indian region again. The theoretical construct is developed to demonstrate the association among different dimensions toward satisfaction. Through well designed questionnaire we analyzed 375 responses through structured equation modeling. Results of the study indicate that perceived quality of services offered drives the choice of a healthcare organization in foreign country and helps in satisfying the patient needs. Further, findings reveal that satisfaction of healthcare tourist does not lead to the intention of visiting again. The study presents implications for administrators, leaders and healthcare workers, that how they can contribute in enhancing the satisfaction of the healthcare tourist. The commitment of healthcare systems to service quality and qualified staff lead to healthcare tourist satisfaction. The study provides a base and reconfirm the healthcare tourism antecedents ranging from perceived quality, experience to treatment outcome.